Captain Superlative - Puller, J. S. (Los Angeles ; Disney-Hyperion, 2018)
Janey, a quiet outsider, is inspired by the eccentric and enigmatic Captain Superlative, a masked superhero who runs through the halls of their middle school, performing radical acts of kindness.
Keywords: Heroes -- Juvenile fiction; Superheroes -- Juvenile fiction; Kindness -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Single-parent families -- Juvenile fiction; Heroes -- Fiction; Superheroes -- Fiction; Kindness -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Single-parent families -- Fiction